Phenomenology Study: Community Non Acceptance of Children with HIV/AIDS in Surakarta - Fetty Rosyadia Wachdin; Bhisma Murti; Argyo Demartoto (Journal of Epidemiology and Public Health, 2016)
Background: There were 13 cases of children with HIV/AIDS in Surakarta in 2016. They were infected from their mothers. These children got stigma and discrimination from the community due to their HIV positive status. This study aimed to describe stigma and discrimination from the community to the children with HIV/AIDS.Subjects and Method: This was a qualitative study with phenomenology approach. This study was conducted at Rumah Singgah Lentera (Halfway House Lentera), Surakarta. The key informants for this study included managers of Rumah Singgah Lentera, fulltime secretary, children with HIV, and community members living in the neighborhood. The data were collected by in-depth interview, and then grouped into coding units and described and analyzed.Results: The community surrounding Rumah Singgah Lentera, Surakarta, viewed children with HIV/AIDS as a disgrace. Various kinds of discrimination such as non-acceptance, alienation, restriction have been addressed by the community to the children with HIV/AIDS. The community has also stigmatized managers of Rumah Singgah Lentera, Surakarta, that they were also HIV infected and made profit of HIV/AIDS donation they received. This stigma occured because of lacking in HIV/AIDS knowledge, particulary its mode of transmission. Stigma and discrimination have caused psychological disorder among children with HIV/AIDS. They often feel sad, alienated, and cry, so that they often withdraw from their social environment. In term they feel dispair and decline to take ARV drugs.Conclusion: there is a need to enhance knowledge in HIV/AIDS, its mode of transmission, method of prevention, and its treatment for the community, in order to repress stigma and discrimination from the community.Keywords: HIV/AIDS, children, stigma, discrimination.Correspondence: Fetty Rosyadia Wachdin. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: fettyrosyadia@gmail.comJournal of Epidemiology and Public Health, 1(3): 148-153https://doi.org/10.26911/jepublichealth.2016.01.03.01